WACANA KRITIS LUDWIG FEARBANG TERHADAP KONSEP AGAMA: STUDI ANALISIS DOGMATISASI AGAMA DI INDONESIA: WACANA KRITIS LUDWIG FEARBANG TERHADAP KONSEP AGAMA: STUDI ANALISIS DOGMATISASI AGAMA DI INDONESIA - Arianingsih, Fadhilatillaili; Kalsum, Umi; Padli Prasitya , Ahmad (ISLAMIKA, 2024)
This study aims to examine Ludwig Feuerbach's critical discourse on the concept of religion: A study on the analysis of religious dogmatization in Indonesia. The research employs a qualitative method with a literature review approach, relying on various primary sources such as books, documents, theses, and journals. The main focus is Ludwig Feuerbach's thoughts on the concept of religion, using relevant journal articles as a reference. At least five sources of literature are utilized, analyzed in depth to provide an understanding of Feuerbach's ideas regarding the dogmatization of religion. The data obtained from the literature are examined for completeness and consistency of meaning. Subsequently, the data are organized to facilitate analysis, ultimately leading to conclusions that address the research questions. The findings of this study reveal that Ludwig Feuerbach's view on the dogmatization of religion emphasizes that religion is a projection of human desires and needs, where God and His attributes are reflections of ideal human traits. In the context of Indonesia, with its rich religious and cultural diversity, this concept invites a more critical and reflective understanding of religion. Strictly applied religious dogmatization can strengthen the identity of certain groups but may also trigger inter-religious and intercultural conflicts. Therefore, the principle of "Bhinneka Tunggal Ika" (Unity in Diversity) must be upheld through inclusive interfaith dialogue to maintain peace and harmony in national and social life.